Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Karyawan 9 Koperasi Di Muara Teweh - Suparman Suparman; Dwi Wahyu A; M. Hasanur Arifin (Universitas Lambung Mangkurat, 2019)
This study aims to (1) examine the effect of partially Motivation (X1) the Employee performance, (2) to test the effect of partially Job Satisfaction (X2) the Employee performance (Y), and (3) test the effect of simultaneous motivation (X1) and Job Satisfaction (X 2) the Employee performance (Y) at 9 cooperatives in Muara TewehSamples taken as many as 51 employees were selected with sampling jenuh technique. Data collection using questionnaire while data analysis using SPSS version 23.00. The test results showed (1) Motivation significant effect on employee performance partially to great effect 53.4%, (2) job satisfaction significantly influence employee performance partially to great effect 22.4%, and (3) Motivation and Job Satisfaction Simultaneously significant effect on Employee Performance with a big influence of 38.3% while the rest of 61.7% in influenced by other variables Keywords: Motivation, Job Satisfaction, Employee Performance